Regulation of tumor necrosis factor-related apoptosis-inducing ligand sensitivity in primary and transformed human keratinocytes - Leverkus, Martin; Krammer, Peter H.; Walczak, Henning (Cancer research, 2000)
Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) has been shown to exert potent cytotoxic activity against many tumor cell lines but not against normal cells. It has been hypothesized that this difference in TRAIL sensitivity between normal and transformed cells might be due to the expression of the non-death-inducing TRAIL receptors (TRAIL-R) TRAIL-R3 and TRAIL-R4, presumably by competition for limited amounts of TRAIL. To assess the regulation of resistance versus sensitivity to TRAIL in primary as well as transformed keratinocytes, we examined TRAIL sensitivity, TRAIL receptor expression, and intracellular signaling events induced by TRAIL. Although TRAIL induced apoptosis in primary as well as transformed keratinocytes, a marked difference in sensitivity could be observed with primary keratinocytes (PK) being 5-fold less sensitive to TRAIL than transformed keratinocytes (TK). Yet both cell types exhibited similar TRAIL receptor surface expression, suggesting that expression of TRAIL-R3 and TRAIL-R4 may not be the main regulator of sensitivity to TRAIL. Biochemical analysis of the signaling events induced by TRAIL revealed that PK could be sensitized for TRAIL and, similarly, for TRAIL-R1- and TRAIL-R2-specific apoptosis by pretreatment of the cells with cycloheximide (CHX). This sensitization concomitantly resulted in processing of caspase-8, which did not occur in TRAIL-resistant PK. These data indicate that an early block of TRAIL-induced apoptosis was present in PK compared with TK or PK treated with CHX. Interestingly, cellular FLICE inhibitory protein (cFLIP) levels, high in PK and low in TK and several other squamous cell carcinoma cell lines, decreased rapidly after treatment of PK with CHX, correlating with the increase in TRAIL sensitivity and caspase-8 processing. Furthermore, ectopic expression of cFLIP long (cFLIPL) in TK by transfection with a cFLIPL expression vector resulted in resistance to TRAIL-mediated apoptosis of these cells. Thus, our results demonstrate that TRAIL sensitivity in PK is primarily regulated at the intracellular level rather than at the receptor level.
Gesehen am 26.04.2021